Thyroid Tissue Connected to Normally Located Thyroid Gland: Ectopic or Exophytic? - Erol Keles; Sule Ozkara; Turgut Karlidag; İbrahim Hanifi Ozercan (Case Reports in Otolaryngology)
Ectopic thyroid tissue is seen rarely. It is often seen in cervical midline, and rarely in other areas such as submandibular area. Diagnosis is made histopathologically by fine needle biopsy after the elimination of malignancy. In the treatment of ectopic thyroid tissue, surgical excision is mostly applied. According to our knowledge, there is no exophytic thyroid tissue reported in the literature. In this paper, a 32-year-old woman who presented with a swelling under the right jaw and found a thyroid tissue attached to the normally located thyroid gland with a fibrous band in the neck was discussed.